2016 IFPRI A-133 (Uniform guide) - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
We have audited the accompanying financial statements of International Food Policy Research Institute (IFPRI), which comprise the statements of financial position as of December 31, 2016 and 2015, and the related statemetns of activities, changes in unrestricted net assets, and cash flows for the years then ended, and the related notes to the financial statements.